Período total de prevenção a interferência das plantas daninhas na cultura da alface cultivar Solaris - Giancotti, Paulo Roberto Fidelis [UNESP] (2010)
This research work aimed to determine the total period of interference of weeds prevention of lettuce cultivar Solaris. The experiment was conducted in Universidade Estadual de Londrina, in the period of autumn/ winter of 2008. The lettuce crop remained free from weed interference from emergence up to 0, 10, 20, 30, 40, 50 e 60 days. The experiment was arranged in a randomized block design with four replications. The weed community was composed by Bidens pilosa, Amaranthus hybridus, Oxalis corniculata, Euphorbia heterophylla, Spinacia oleracea, Commelina benghalensis e Lepidium virginicum. It was determined dry and fresh matter of weeds, and number of lettuce leaves. Assuming a tolerance of 5% for crop production decrease, it was verified that the total period of interference prevention (TPIP) occurred up to 21 days after transplanting. Weed interference throughout the crop cycle reduced 25% of its yield.